Analysis of Politeness Strategies on Comments in Influencers Instagram Account - Siti Aminatus Sholehah; Zaenul Wafa (Journalistics: Journal of English Teaching and Applied Linguistics, 2023)
This study aims to find out the types of politeness strategies and identifying the most dominant type of politeness strategy used by netizens on Comments Influencer Instagram accounts. The research design of the study is qualitative descriptive. The data of this research collected from netizens’ comments on Influencers Instagram accounts. The data collection of thus research are observing and documenting. To get the data, the researcher used screenshot comment from Influencers Instagram account. The findings show that were 45 comments consisting of 3 Influencers accounts, each account analyzed 15 comments. In total, there are 22 Positive Politeness, 4 Negative Politeness, 11 Bald on Records, and 8 Off Records. It can be concluded that the most dominant type of politeness strategy used by netizens are Positive Politeness.